Silicon/Biomass Carbon Composite as a Low-Cost Anode for Lithium-Ion Batteries - Ziying Meng; Ziqing Xu; Heng Li; Hanqing Xiong; Xijun Liu; Chunling Qin; Zhifeng Wang (Energies)
Various biomass materials have been developed as precursor materials to fabricate carbon-based anodes for Li-ion battery (LIB) applications due to their inherent sustainability and low cost. However, the low theoretical specific capacity of carbon materials (273 mAh g−1) restricts their further application as an anode for LIBs. Herein, silicon/reed catkin composites (Si/RC) and silicon/apricot shell-derived carbon (Si/AC) are successfully fabricated, and their performances are evaluated as anode materials for LIBs. The Si/RC anode displays a reversible capacity of 318.4 mAh g−1 after 100 cycles at 200 mA g−1 and remains 229.3 mAh g−1 after 1000 cycles at 1 A g−1. This work discloses the feasibility and promising prospects of utilizing biomass reed catkins to prepare low-cost, porous, carbon-based materials for energy storage applications.